1978
DOI: 10.1104/pp.61.6.878
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Membrane Permeability of Winter Wheat Cells following Freeze-Thaw Injury as Determined by Nuclear Magnetic Resonance

Abstract: Nuclear etic resoaace (NMR) relaxation times were studied in acclhnated and nonacclmated Kharkov It has been inferred by many investigators that membranes, primarily plasma membranes, are the site of freezing injury. This evidence is based upon loss of semipermeability properties of the membrane following freezing injury (7,19).Pulse NMR3 measurements of the longitudinal relaxation time (T1) and the transverse relaxation time (T2) have been used to study water and water interactions in biological systems (5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

1980
1980
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 18 publications
(26 reference statements)
3
16
0
2
Order By: Relevance
“…3). T 2 values of long fraction in the grains at milky and dough stages were around 100ms showing the existence of free water (Chen and Gusta, 1978). T 2 values of the short fraction in the grains grown at 20ºC were between 10 and 90 ms, and did not change until 29 DAF but dropped sharply to 20 µs at 36 DAF (Fig.…”
Section: Relationship Between Nmr Relaxation Timesmentioning
confidence: 84%
“…3). T 2 values of long fraction in the grains at milky and dough stages were around 100ms showing the existence of free water (Chen and Gusta, 1978). T 2 values of the short fraction in the grains grown at 20ºC were between 10 and 90 ms, and did not change until 29 DAF but dropped sharply to 20 µs at 36 DAF (Fig.…”
Section: Relationship Between Nmr Relaxation Timesmentioning
confidence: 84%
“…T 2 in the long fraction indicating over 200 ms is thought to be mainly associated with vacuole and the fraction with the short T 2 less than 60ms is thought to be associated with the cytosol and apoplastic region in the leaves (Chen and Gusta, 1978). The prolongation of T 2 in the long fraction was accompanied by a gradual increase in signal intensity in the temperature range from 0 to -20ºC.…”
Section: Infl Uences Of Cold Stress On T 2 In Organsmentioning
confidence: 77%
“…Furthermore, the leakage of electrolytes indicated that both leaves and roots exposed to subzero temperatures were severely damaged ( Table 2). The shortening of T 2 has been attributed to a decline in membrane permeability under freezing injury in wheat crowns (Chen and Gusta, 1978). Therefore, the abrupt shortening of T 2 suggested that two water components in leaves froze at -20 to -25 ºC and those in roots froze at -10ºC.…”
Section: Infl Uences Of Cold Stress On T 2 In Organsmentioning
confidence: 99%
“…Além do dano físico, podem ocorrer modificações na composição química da parede celular e na permeabilidade da membrana plasmática, que podem também influenciar na quantidade e qualidade do extrato final obtido (Palta et al, 1977;Olien & Smith, 1977;Chen & Gusta, 1978;Weiser et al, 1990;Murai & Yoshida, 1998).…”
Section: Armazenamento De Extratos E De Raízesunclassified
“…Em muitos estudos, a extração de sorgoleone tem sido feita a partir de raízes recém-coletadas, e o extrato é usualmente armazenado em baixas temperaturas antes da sua utilização em testes de atividade e do seu fracionamento (Einhelling & Souza, 1992;Rasmussen et al, 1992;Nimbal et al, 1996;Souza et al, 1999;Kagan et al, 2003;Czarnota et al, 2003b;Hejl & Koster, 2004). Alguns estudos mostram que o armazenamento de órgãos vegetais antes da extração pode acarretar alterações no extrato final obtido (Palta et al, 1977;Olien & Smith, 1977;Chen & Gusta, 1978;Weiser et al, 1990;Murai & Yoshida, 1998). Além disso, as condições de armazenamento de extratos vegetais podem influenciar na estabilidade e degradação dos compostos químicos presentes (Srivastava et al, 2007;Tabart et al, 2007).…”
Section: Introductionunclassified